Teori Receptie, dan Teori Receptie a Contrario dalam Pusaran Muslim Minoritas dan Muslim Mayoritas di Indonesia - Lucky Omega Hasan (Jurnal Syntax Admiration, 2023)
This research investigates the application of the Reception Theory and Reception Theory A Contrario in the context of minority and majority Muslim communities in Indonesia. Through literature studies, case analyses, interviews, and contrastive analysis, this research aims to understand the impact of using both of these theories on the social reality in regions with different characteristics. The research results indicate that, although they hold academic value, the Reception Theory and Reception Theory A Contrario are not in line with the factual conditions of society in Indonesia, particularly in Aceh and Bali. The application of these theories has the potential to create conflicts between the majority and minority Muslim communities. Therefore, the author concludes that the Reception Theory and Reception Theory A Contrario should not be used as the main theories or references in regulating the application of Islamic law in Indonesia. Instead, a more inclusive approach is needed that can accommodate the cultural and religious diversity in Indonesia. This research provides a new contribution to the discussion on the relevance of Islamic law theories in the multicultural social context of Indonesia.